Sphaerotheca Fuliginea (Powdery Mildew) Parasitic on Macrotyloma uniflorum (Gahat): a Fungus New to Nepalese Mycoflora - Adhikari, Mahesh Kumar (Journal of Natural History Museum, 2015)
The powdery mildew (a fungus) Sphaerotheca fuliginea (Sch.: Fr.) Poll., parasitic on Macrotyloma uniflorum (Lam.) Verdc (Gahat) is recorded as new addition to Nepalese mycoflora. The description and distribution to the species is provided herewith. J. Nat. Hist. Mus. Vol. 28, 2014: 171-174